Penerapan Senam Pancasila dalam Mengembangkan Motorik Kasar Siswa Taman Kanak-kanak: Application of Pancasila Gymnastics in Developing Gross Motor Skills of Kindergarten Students - Rezki Rezki; Andi Rezky Nurhidaya; Riskal Fitri (Madrasah Tsanawiyah DDI Cilellang, 2023)
Delays in children’s gross motor development are still common. Therefore, activities are needed that can stimulate children's gross motor development so that it can develop quickly and optimally. This study aims to (1) describe Pancasila gymnastics activities in kindergarten students and (2) analyze the implications of Pancasila gymnastics on children's gross motor development in kindergarten students. This type of research is qualitative with a descriptive approach. The object of research is group B1 students of Gita Ananda Kindergarten, Makassar City. The results of this study indicate that the application of Pancasila gymnastics activities is carried out through direct practice by the teacher using a projector and speaker. This method can attract children’s attention to follow or do Pancasila gymnastics movements. This method makes children actively participate in performing gross motor movements according to what they see. In addition, Pancasila gymnastics has implications for children’s gross motor development. This research has implications for the importance of learning programs that train students' gross motor skills in kindergarten. This program is well prepared and implemented with methods that attract students so that they are interested in following movements that train their gross motor skills.